A new species of the genus Dulichiella Stout, 1912 (Crustacea: Amphipoda: Melitidae) from Pecém Harbor, Ceará state, Brazil - Alves, Jessika; Johnsson, Rodrigo; Senna, André R. (Zootaxa, 2014)
A new species of the genus Dulichiella Stout, 1912 is described for the Northeastern Brazilian coast. The new species is recognized from the others in the genus by presenting (1) the accessory flagellum 5-articulate, (2) distolateral crown of gnathopod 2 of males with 4 spines, (3) Maxilla 1 inner plate, outer plate and palp distally enlarged and rounded, and (4) Pereopods 6 and 7 without bunches of long setae. This is the second species of Dulichiella recorded from South Atlantic and Brazilian waters.